2000
DOI: 10.1260/1351010001501480
|View full text |Cite
|
Sign up to set email alerts
|

Field Measurement and Criteria for Sound Insulation between Dwellings in Europe

Abstract: Airborne and structure-borne sound transmission are the dominant noise paths in terraced, semi-detached houses and in multi-storey buildings, often causing annoyance when heard. They usually are controlled by applying building regulations before, during and after the construction of the dwellings. As part of a comparative study of the control and promotion of quality in housing in Europe, the acoustic quality in dwellings have been investigated for France, Norway, Sweden, the Netherlands, Germany, Switzerland,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is well established that one of the main noise source in residential buildings is domestic noise [1,2,3,4]. Severe problems with annoyance among habitants were caused by poor sound insulation in existing dwellings In Italy, despite the regulation concerning requirements for sound insulation between dwellings, DPCM 5/12/97 [5], is fourteen years old, still many buildings haven't a sufficient acoustic comfort.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that one of the main noise source in residential buildings is domestic noise [1,2,3,4]. Severe problems with annoyance among habitants were caused by poor sound insulation in existing dwellings In Italy, despite the regulation concerning requirements for sound insulation between dwellings, DPCM 5/12/97 [5], is fourteen years old, still many buildings haven't a sufficient acoustic comfort.…”
Section: Introductionmentioning
confidence: 99%
“…The average reverberation in British living rooms has been considered to be 0.5 seconds since Perkin et al reported in the early 1960's [1] that "the rever beration time of furnished living rooms is usually about 0.5 sec at most frequencies within the range of interest" (100 to 3150 he). The value of 0.5 see is used as the reference reverberation time for the normalising of field measurements of sound insulation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main causes of acoustic feeling of discomfort in buildings is due to external noise sources (such as road traffic, rails, planes, industrial plants, etc.) which propagate in particular through the glazed systems which are generally the weakest part of the façades [1]. The increase of environmental noise and the search for greater acoustic comfort inside the buildings have led to the technological development of innovative façade systems, improving overall acoustic performances [2][3].…”
Section: Introductionmentioning
confidence: 99%